Impediments to Agricultural Production in Uganda and Measures to Enhance Soil Fertility Utilizing Organic Soil Amendments: A review - Nabyonga, Lydia; Basamba, Twaha Ali; Nyakoojo, Clement; Ssenku, Jamilu E. (Cogent Food & Agriculture, 2022)
Agriculture is the greatest resource that supports life on earth. The rapidly growing human population has globally escalated the demand for agricultural products including; food, fodder, medicines, and biofuels, but their supply has been limited. This has been attributed to the gradually declining quality and quantity of natural resources. The agricultural sector in Uganda has suffered from the effects of land-use shift as one of the major challenges contributing to land degradation. This has been aggravated by poor soil management practices leading to low soil productivity. The global campaign to adopt fertilizer use has generated significant outcomes in boosting production but with severe consequences of environmental pollution from the bulky fertilizers used. This review paper seeks to identify bottlenecks in the line of agricultural production and environmental sanitation in Uganda, with a proposed alternative of using well-processed organic fertilizers from biomass and nano-fertilizers postulated to eliminate fertilizer bulk. The paper further highlights Azolla as one of the high biomass plants with potential agricultural benefits when used as an organic fertilizer. The literature search for this review paper was based on the information published on the web of science and extracts from interviews. All authors recommended the adoption of safer organic and nano-fertilizer technologies as the alternative solution to improving soil productivity while promoting environmental sanitation in Uganda.
Keywords: Agricultural production; Soil fertility; Organic soil amendments; Biomass plants